Diversity of Macrolichens in Bolampatti II Forest Range (Siruvani Hills), Western Ghats, Tamil Nadu, India. (4th September 2013) - Balaji, P.; Hariharan, G. N.
Abstract : An annotated checklist of 103 macrolichen species is provided based on identification of specimens collected from three different vegetation types within the Bolampatti II forest range, Western Ghats, India. Among them, the dominant order is Lecanorales with 47 species, while the dominant family is Parmeliaceae with 40 species. The foremost genus is Usnea with 15 species.